“I am not a victim, I am a survivor”: healthy sexuality as a context for resilience in women survivors of childhood sexual abuse - Newsom, Kimmery C. (Kansas State University, 2013)
The current study was conducted with women survivors of childhood sexual abuse (CSA) about their experiences of resilience in the context of interpersonal and sexually intimate relationships. Six women between the ages of 18 and 55, who self-identified as resilient on the pre-screening form, were invited to participate in the study. Qualitative methods with a phenomenological lens were employed. One-on-one interviews were conducted with participants. The results revealed the perspective and focus the survivors have regarding resilience and sexuality in interpersonal relationships. The participants had very similar thought patterns, which supports the idea that women survivors who self-identify as resilient have very similar experiences when it comes to resilience, relationship functioning and the view of themselves as sexual beings. Some of the main themes that emerged included but were not limited to bouncing back, moving forward, determination, confidence, use of voice, safe, loving relationships, empowered, church, God, religion, etc. Although each woman’s experience is not exactly the same, their views regarding their mental, emotional, and physical experiences as survivors of CSA were very similar.
Keywords: Sexuality; Survivors; Childhood sexual abuseResilience; Individual & Family Studies (0628)